ZnO nanowire-immobilized paper matrices for visible light-induced antibacterial activity against Escherichia coli. Issue 3 (5th June 2015) - Chauhan, Indu; Aggrawal, Sudiksha; Mohanty, Paritosh
<x xml:space="preserve">Abstract</x> ZnO nanowire-immobilized paper matrices were made by a single-step hydrothermal method which kill E. coli under visible light.